Medical Referral-Based Exercise Programs for Physical Activity and Healthy Behavior Change - Mahsa Hakimi Poor; Kerry Clarke; Thawatchai Lukseng (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2026)
Purpose of the study: This study aimed to examine the outcomes of medical referral-based exercise programs in improving physical activity participation, adherence, and healthy behavior change among community populations at risk of physical inactivity and non-communicable diseases. Methodology:A mixed-methods design was employed by integrating quantitative physical activity assessments, exercise referral monitoring data, qualitative interviews, and evaluation of a community-based exercise intervention. Physical activity levels were assessed using the International Physical Activity Questionnaire and General Practice Physical Activity Questionnaire, while qualitative data were analyzed using Interpretative Phenomenological Analysis. Main Findings: The findings indicated that participants adhering to exercise referral programs demonstrated increased physical activity levels, with improvements of approximately 1,000 metabolic equivalent minutes per week. The International Physical Activity Questionnaire showed a weak association with the General Practice Physical Activity Questionnaire in assessing physical activity levels. Programs incorporating Motivational Interviewing demonstrated higher adherence rates compared with conventional referral approaches, suggesting potential benefits for supporting sustainable healthy behavior change. Novelty/Originality of this study: This study integrates quantitative and qualitative evidence to compare conventional referral schemes with Motivational Interviewing-based interventions in community healthcare settings. The findings provide updated evidence-based recommendations for developing more effective medical referral-based exercise programs and contribute practical insights for strengthening physical activity promotion strategies